The speech therapist's professional overcoming, perspectives stops to the development of the oral communication (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The speech therapists' professional overcoming constitutes a need to confront the attention to primary pupils of the educational level successfully to the oral communication. So that you assure the systematic bringing up to date, the perfecting of the performance, the development of loud professional competitions. As well as the enrichment of his cultural wealth that it enables his exact fulfillment of the shows with effectiveness. This allows justifying the need to accomplish a new theoretic construction to explain the speech therapist's process of professional overcoming; As from the systematization of the contents with an epistemic integrative logic that you be based on the specification, integration and contextualization of the contents. The objective of the present article is intended to design the professional overcoming of the  speech therapist as from the systematization of the contents, that the developments favor the oral communication in the pupils of the educational level primary. Bayamon takes ten speech therapists' sign of the municipality for it than labor in the educational level primary.
Keywords: professional overcoming; speech therapist; pupil; oral communication